Factors Inhibiting BPJS Receivables Disbursement in Improving Financial Performance (Case Study at Multazam Hospital in Gorontalo): Faktor-Faktor Penghambat Pencairan Piutang Bpjs Dalam Meningkatkan Kinerja Keuangan (Studi Kasus Di Rs. Multazam Gorontalo) - Nur Fadila Bahmid; Lisda Van Gobel; Yahya Antu (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
This study aims to understand the factors hindering the settlement of BPJS receivables and their impact on the financial performance of RS Multazam Gorontalo. This research adopts a qualitative descriptive approach. The findings reveal several inhibiting factors, such as a shortage of skilled coding personnel, a low rate of document returns by BPJS, a budget deficit in BPJS Health due to unpaid premium contributions, and delayed disbursement of BPJS patient claim funds. RS Multazam has utilized the SCF program to address cash flow issues. Recommendations include recruiting more coding personnel, providing training for BPJS patient document verification, minimizing document return issues, utilizing integrated applications, and efficiently utilizing government SCF programs. All of these actions are aimed at improving cash flow and hospital operations